Policy perspectives for international trade and economic relations - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1972)
The book talked about the opportunities for further progress towards the general objective of a greater liberalization of international trade.
gau 23/02/17
Loans
Keywords: Commercial policy; International economic relations; International finance